Investigation of Groundwater Potential using Electrical Resistivity Method and Hydraulic Parameters in Lam Apeng, Aceh Besar, Indonesia. - Dian Darisma; Ferdy Fernanda; Muhammad Syukri (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Lam Apeng is a village with a majority of people living as farmers, which causes the need of water for agriculture is increasing. The water demand in this area continues to increase as the population increases, for various purposes. The objective of this study is to determine the distribution of the groundwater layer using the electrical resistivity method and to determine groundwater potential using hydraulic parameters. This research is conducted using 2 measurement line with a length of each line is 112 meters and distances of each electrode is 2 meters. The data invert using Res2Dinv software to obtain 2D subsurface lithology subsurface. At line 1, the aquifer (sand) layer is located in the second layer with a rock resistivity value of 12 Ωm - 18.6 Ωm at a depth of 8 m - 18 m. At line 2, the aquifer (sand) layer is also located in the second layer with a resistivity value of 4.6 Ωm - 18 Ωm at a depth of 5 m – 12 m. Based on the interpretation of the two measurement lines, it can be concluded that the type of aquifer in the research site is a semi unconfined aquifer. In this study, hydraulic parameters (hydraulic conductivity, longitudinal conductance, transverse resistance, and transmissivity) was calculated based on the resistivity value and the thickness of the aquifer layer. The average resistivity of the aquifer layer used is 15.3 Ωm and 11.3 Ωm, respectively for line 1 and line 2, indicating that the aquifer was moderately corrosive. Longitudinal conductance values are 0.65 Ω-1 and 0.62 Ω-1 which indicated moderate protective capacity. The transmissivity values are 6.78 m2/dayand 4.77 m2/day, which indicates that the designation in this area is low and the groundwater potential is local or only for personal consumption.